Eco Cooler for Cooler House without Electricity for Educational Purposes - Antonio, Alvito; Hasanah, Maulidah; Damayanti, Novita; Devina, Oryza Aprilia; Khoerunnisa, Fitri; Winarno, Nanang (Indonesian Journal of Multidiciplinary Research, 2021)
The earth's temperature from 1981 to February 2021 has relatively increased. The increase in temperature on earth has made many people choose to use air conditioning so that the temperature in their homes is not too cold. The energy demand from air conditioning worldwide will be three times as much by 2050. Bangladesh has created a system called the Eco-Cooler as an alternative to lowering room temperature without using large electrical energy so as to save energy and costs. The eco-cooler can reduce temperatures from 1-3˚C in a room with a size of 4.2 × 4.2 × 3.3 m3 using an Eco-cooler with a bottle diameter of 6 cm and a board area of 48 × 48 cm2. This can be a good educational point for being applied in Indonesia. The advantage of using the Eco-Cooler is that it is easy to maintain, easy to use, the air is more humid, and it saves energy.